Estudio de la valoración de los peritajes psicológicos en las víctimas de delitos en el proceso penal - Bustamante Álvarez, Eliana Elizabeth (2023)
This Degree Project is entitled: Study of the assessment of psychological expertise in victims of crimes in criminal proceedings"; This analysis arises from the interest that I was given to investigate an existing legal vacuum on the part of the State in terms of the number of sessions and the way in which psychological assessments are carried out within the expert reports, the same ones that are practiced by officials of the Attorney General's Office of the State, that even at the moment of being able to talk with psychologists who are experts in the subject and to be able to analyze some psychological reports published within an investigation, it is believed convenient that at least two to three sessions be carried out in order to determine the degree of affectation in victims of a crime, it is important to make it known that these sessions must have a sequence to follow based on the facts raised and the type of victim to whom this assessment is going to be made, in the same way as the bibliography, the test and techniques are duly updated taking into account that science has advanced according to the passage of time. However, it is found within article 511 of the Comprehensive Criminal Code in its numeral 6 in detail everything that a periodic report must contain, but it does not specify the number of sessions nor that its techniques and tests are correctly updated to subsequently be applied according to the scientific foundation, the same that served as a basis at the time of making the recommendations and conclusions of the case that is being carried out. Regarding article 7 of the Resolution of the Instructions of the State Attorney General's Office regarding the expert report, it specifies that the report must be delivered within the date provided, taking into account the points established by the Comprehensive Organic Criminal Code, which is why with respect to the testimony of the experts before the support of the result of the psychological report, there is no established corroboration of the information that is reflected in the expert opinion, which would improve for the prosecuted subjects that this means of evidence that is presented and analyzed can be verified on trial; without forgetting that elements of conviction are determined that help determine relevant information within the process. In the present degree work, materials and methods were applied that allowed the development of the investigation, likewise interviews and surveys were carried out with legal professionals and specialized advisors, the results obtained served to propose proactive guidelines with the purpose of allowing to determine the degree of total affectation on the victims, but not that presumptions are made within these expert reports, taking into account that within a criminal proceeding the expert report carried out on the victim is admitted as expert evidence.